The THE INFLUENCE OF WORDS RECOGNITION IN READING COMPREHENSION TO NINTH GRADE STUDENT OF MTSN LANGS - Fadlia Fadlia (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
The influence of word Recognition in Reading comprehension to Ninth Grade Students of MTsN Langsa. Words are basic element to language learning. The learners are required master them as well as possible in order that they can use them as a tool of communication. To extract the information from the text very much depends upon the knowledge of word the readers live. The sample of this study was the students of MTsN Langsa who were in the ninth grade in the academic year of 2017/2018. In this study the researcher took one class only randomly. The purpose of this writing was intended to know the influences of word recognition to students’ ability in reading comprehension. In this researcher the researcher tries to describe the result of a research of the effect of the word recognition skill on student’s reading comprehension achievement. The data are collected by using a text in MTsN Langsa, Kota Langsa. The word recognition test consists of 40 questions. Since this researcher dealt with the correlation between two variables, the appropriate statistical procedure is person’s product moment correlation formula.